2015
DOI: 10.1016/j.genhosppsych.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical factors associated with benzodiazepine prescription at discharge from psychiatric inpatient treatment

Abstract: Objective We sought to characterize diagnostic and treatment factors associated with receiving a prescription for benzodiazepines at discharge from a psychiatric inpatient unit. We hypothesized that engaging in individual behavioral interventions while on the unit would decrease the likelihood of receiving a benzodiazepine prescription at discharge. Method This is an observational study utilizing medical chart review (n = 1007) over 37 months (2008–2011). Descriptive statistics characterized patient demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…[10,[15][16][17] Epidemiological data suggest that females tend to have a higher prevalence of depression and anxiety than males, which are common therapeutic indications for BZDs. [2,22] This correlates with our finding that depression and depression and anxiety were the therapeutic conditions most often treated with a regimen that included a BZD. Additionally, studies suggest that females are more inclined to use medication and access health services than males, resulting in a greater likelihood of BZD use.…”
Section: Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…[10,[15][16][17] Epidemiological data suggest that females tend to have a higher prevalence of depression and anxiety than males, which are common therapeutic indications for BZDs. [2,22] This correlates with our finding that depression and depression and anxiety were the therapeutic conditions most often treated with a regimen that included a BZD. Additionally, studies suggest that females are more inclined to use medication and access health services than males, resulting in a greater likelihood of BZD use.…”
Section: Researchsupporting
confidence: 81%
“…[2] The second most common therapeutic indication for BZD prescribing was depression. Studies in the USA have found depression to be the most common therapeutic indication for BZD prescription upon discharge, [13,22] while in developing countries such as Thailand and Lebanon depression has been identified as the third most common therapeutic indication. [19,26] These findings demonstrate the worldwide prevalence of BZD use in depression.…”
Section: Researchmentioning
confidence: 99%
“…In this respect, female patients were found to be more frequently BZD users in several reports. For instance, Peters and colleagues analyzed multiple demographic and clinical factors associated with BZD prescription at patients' discharge from psychiatric unit, reporting that women had a greater likelihood of receiving BZDs (Peters, Knauf, Derbidge, Kimmel, & Vannoy, ). Also Demyttenaere and colleagues, in the ESEMeD study, reported that, beyond specific clinical factors, female gender was more frequently associated with BZD use in the last year (Demyttenaere et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with psychiatric disorders are particularly exposed to benzodiazepines and represent a very different population study than those usually considered when assessing the patterns of benzodiazepine use even when considering only older patients . Misuse of benzodiazepines might be more frequent when they are prescribed by a psychiatrist .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Based on the National Institute for Health and Care Excellence guidelines, many countries recommend that benzodiazepine treatment should not exceed 4 consecutive weeks. [10][11][12] Patients with psychiatric disorders are particularly exposed to benzodiazepines 13,14 and represent a very different population study than those usually considered when assessing the patterns of benzodiazepine use even when considering only older patients. 15 Misuse of benzodiazepines might be more frequent when they are prescribed by a psychiatrist.…”
mentioning
confidence: 99%